FILSAFAT AKHLAK DALAM PEMIKIRAN IBNU MISKAWAIH DAN AL-GHAZALI (STUDI KOMPARATIF) - Ummul Latifa; Nelmaya Nelmaya (CV. ADIBA AISHA AMIRA, 2024)
One of the main missions in Islam is to perfect human morals. Morals are very important and fundamental, because with morals can be determined the measure of all human actions, good bad, right wrong, halal and haram. Humans without morals will lose their human dignity as the most noble creatures of Allah. In this case, Ibn Miskawaih and Al-Ghazali expressed their opinions regarding the Philosophy of Morals, having the same opinion regarding the investigation of Morals must begin with knowledge of the soul, its strength and even its characteristics. The type of research used is qualitative research which is library research. The primary data sources were obtained from the library books by Ibn Miskawaih